2020
DOI: 10.1001/jamanetworkopen.2020.17513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Case Volumes of a Heart Transplant Program and Short-term Outcomes After Changes in the United Network for Organ Sharing Donor Heart Allocation System

Abstract: IMPORTANCE Institution-level strategic changes may be associated with heart transplant volume and outcomes. OBJECTIVE To describe changes in practice that markedly increased heart transplant volume at a single center, as well as associated patient characteristics and outcomes. DESIGN, SETTING, AND PARTICIPANTS A pre-post cohort study was conducted of 107 patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Similar to our findings, several studies demonstrate increased ischemic time and decreased waitlist time in the postchange era 27–32 . Some studies suggest that the new system is protective against waitlist mortality 28,30 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our findings, several studies demonstrate increased ischemic time and decreased waitlist time in the postchange era 27–32 . Some studies suggest that the new system is protective against waitlist mortality 28,30 .…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, a study of 3032 heart transplant recipients in the postchange era showed no difference in waitlist mortality 31 . In the postchange era, the use of temporary MCS devices occurs more frequently than durable left ventricular assist devices as a bridge to transplantation 27–32 . Temporary MCS devices are associated with an increased risk for mortality after transplantation, thereby provoking concern for consequential survival outcomes 33–35 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, over 50% of donor hearts offered in the United States are rejected for OHT 19 . Donor hearts with unclear acceptability patterns tend to be outside of the traditionally accepted donor criteria but may still be potentially suitable for transplantation 3 . Furthermore, considering that centers with more aggressive donor acceptance rates have been shown to have superior post-OHT outcomes when compared to centers with lower volumes 20 , uncertainty exists as to if there is a volume-relationship between the use of ECDs in OHT and if an association exists between ECD recipient's outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac transplantation remains the gold standard treatment for end stage heart failure 1 , and despite the growing prevalence of advanced heart failure in the United States, donor heart supply critically limits rates of OHT 2 . This supply and demand mismatch is magnified by the fact that over 50% of offered donor hearts are not accepted for transplantation 3 . The reduced utilization of certain donor hearts is largely tied to the practice of rejecting organs that fall outside of strict donor selection criteria.…”
Section: Introductionmentioning
confidence: 99%
“… 27 - 29 For example, the group from Yale University recently reported dramatic increases in their program volume by accepting older donors, and by prioritizing temporary mechanical circulatory support. 30 …”
mentioning
confidence: 99%